Membranes with Surface-Enhanced Antifouling Properties for Water Purification - Nima Shahkaramipour; Thien N. Tran; Sankara Ramanan; Haiqing Lin (Membranes, 2017)
Membrane technology has emerged as an attractive approach for water purification, while mitigation of fouling is key to lower membrane operating costs. This article reviews various materials with antifouling properties that can be coated or grafted onto the membrane surface to improve the antifouling properties of the membranes and thus, retain high water permeance. These materials can be separated into three categories, hydrophilic materials, such as poly(ethylene glycol), polydopamine and zwitterions, hydrophobic materials, such as fluoropolymers, and amphiphilic materials. The states of water in these materials and the mechanisms for the antifouling properties are discussed. The corresponding approaches to coat or graft these materials on the membrane surface are reviewed, and the materials with promising performance are highlighted.